A new species of the hermit crab genus Catapagurus A. Milne-Edwards, 1880 (Decapoda: Anomura: Paguridae) from the Ryukyu Islands, Japan - Komai, Tomoyuki (Zootaxa, 2024)
A new species of the pagurid hermit crab genus Catapagurus A. Milne-Edwards, 1880, is described based on a single male specimen from off Okinawa Islands, Ryukyu Islands, southwestern Japan, at a depth of 150 m. Catapagurus cracens sp. nov. appears closest to C. tenuilamina Komai, Miller & Malay, 2022 among the 27 congeners, but is distinguished from the latter by some minor morphological features, including the more stout ultimate article of the antennular peduncle, unarmed coxae of the chelipeds, the absence of spiniform setae on the dorsal margins of the propodi of the second and third pereopods and the different shape of the terminal cleft of the telson, as well as the living colouration. Sequences of the two mitochondrial markers (16S rRNA and COI genes) were generated for the new species. Although sequences of the COI gene are not available for any congeneric species, the high pairwise genetic divergence of the 16S rRNA gene (11.7%) supports the new taxon as distinct from C. tenuilamina.